The investigation of mix design approach using waste concrete material as cement replacement material for green construction technology. - Abas, Noor Faisal (Universiti Sains Malaysia, 2015)
The use of concrete in development is essential in the construction industry and it became the most important and major construction materials use all over the world. The concrete is consists of the coarse aggregate, fine aggregate and cement as the binder materials. This research presents an experimental study of the influences of different percentage waste concrete ash use as cement replacement materials to form a new concrete.